The adolescents’ psychosocial functioning inventory (APFI): scale development and initial validation using exploratory and confirmatory factor analysis (2015)
Most of the existing measures of psychosocial functioning among adolescents are developed outside Lower-middle income countries (LMIC). Measures relevant to the LMIC setting will provide opportunity to assess the functioning of adolescents in these settings based on their background or context. The Adolescents’ Psychosocial Functioning Inventory (APFI) which addresses relevant challenges and expectations of adolescents in the LMIC settings was developed to bridge this gap in knowledge. A total of 753 adolescents from purposively selected secondary schools participated in this study. Preliminary analyses were performed using descriptive statistics. The underlying factor structure of the APFI was explored using Exploratory and confirmatory Factor Analysis. Chi-square Goodness of Fit (CGF) and other fit indices were used to assess model fit. Cronbachs alpha was used to assess the reliability of the items and subscales of the APFI. The final model derived from the factor analyses yielded a 23-item three-factor model that provided the best fit to the data. Estimate of overall reliability of the APFI scale was   0.83 while all three factors/subscales: Optimism and Coping Strategy (OCS), Behaviour and Relationship Problems (BRP), and General Psychosocial Dysfunctions (GPD) had moderate to high reliability (   0.59 for OCS,   0.57 for BRP and   0.90 for GPD). The CGF yielded 2 / df  3 =1.58 while all other fit indices were in the acceptable range. The three-factor model APFI is a reliable measure for assessing psychosocial functioning among adolescents in the LMIC.